P705 Switching from originator to biosimilar infliximab—real-world data from 18 months prospective follow-up of a single-centre IBD population. (16th January 2018) - Hoivik, M L; Buer, L C; Bolstad, N; Moum, B; Medhus, A W
Abstract: Background: Long-term clinical data after switching from the originator infliximab to the biosimilar CT-P13 are sparse. Concerns about increased immunogenicity after switching have been raised. We aimed to prospectively study the long-term effectiveness and immunogenicity after switching from originator infliximab to CT-P13 in a single centre, real-life IBD population. Methods: All adult IBD patients treated with originator infliximab at our IBD unit, were switched to CT-P13 during September to November 2015 and followed prospectively for at least 18 months. The primary endpoints were the proportion of patients remaining on medication and the proportion of patients who developed anti-drug antibodies (ADA) 18 months after switching. The secondary endpoints included disease activity scores (Harvey–Bradshaw Index and Partial Mayo Score), C-reactive protein, haemoglobin, faecal calprotectin, infliximab dose and interval, and p -infliximab—all measured at three month intervals. Results: In total, 143 IBD patients were switched, 99 with Crohn's disease and 44 with ulcerative colitis. Median time on originator infliximab before switching was 81 months (IQR 55). Altogether, 131 (92%) patients remained on CT-P13 throughout 18 months follow-up. Six patients developed transient ADA at low levels (10 to 29 AU/l) without any signs of loss of response. Two patients developed ADA at moderate levels (30 to 50 AU/l) and stopped CT-P13. One of these patients had concurrent clinical loss of response whereas the other stayed in clinical remission. Another nine patients stopped CT-P13 during follow-up (one due to loss of response without ADA, four due to adverse events, and four in remission with a personal wish to stop). One patient was lost to follow-up. There was no overall change in disease activity scores, C-reactive protein, haemoglobin, faecal calprotectin, infliximab dose and interval or p -infliximab during 18 months follow-up. Conclusions: The vast majority of patients remained on CT-P13 and disease activity was unchanged during 18 months follow-up after switching. Only 1.4% of the patients developed anti-drug antibodies with clinical implications. This indicates that switching from originator to biosimilar infliximab does not affect the long-term clinical outcome.